Comparison between two newborn screening strategies for cystic fibrosis in Argentina: IRT/IRT versus IRT/PAP. Issue 1 (2nd November 2020) - Teper, Alejandro; Smithuis, Fernando; Rodríguez, Viviana; Salvaggio, Orlando; Maccallini, Gustavo; Aranda, Claudio; Lubovich, Silvina; Zaragoza, Silvina; García‐Bournissen, Facundo
Abstract: Background: The benefits of early cystic fibrosis (CF) detection using newborn screening (NBS) has led to widespread use in NBS programs. Since 2002, a two‐stage immunoreactive trypsinogen (IRT/IRT) screening strategy has been used as a CFNBS method in all public maternity units in the City of Buenos Aires, Argentina. However, novel screening strategies may be more efficient. The aim of this study is to prospectively compare two CFNBS strategies: IRT/IRT and IRT/PAP (pancreatitis‐associated protein). Methods: A two‐year prospective study was performed. IRT was measured in dried blood samples collected 48–72 h after birth. When an IRT value was abnormal, PAP was determined, and a second visit was scheduled to obtain another sample for IRT before 25 days of life. Newborns with a positive CFNBS were referred for a confirmatory sweat test. Results: There were 69, 827 births in the City of Buenos Aires during the period studied; 918 (1.31%) had an abnormal IRT. A total of 207 children (22.5%) failed to return for the second IRT, but only two PAP (0.2%) were not performed. IRT/IRT was more likely to lead to a referral for sweat testing than IRT/PAP (odds ratio 2.3 [95% confidence interval 1.8–2.9], p < .001). Sensitivity and specificity were: 80% and 100% and 86.5% and 82.6% for IRT/IRT and IRT/PAP strategies, respectively. Conclusion: The IRT/PAP strategy is more sensitive than IRT/IRT and has similar specificity; it avoids a second visit and unnecessary sweat testing, and it reduces loss to follow‐up in our population.